INOVASI TEKNOLOGI RAMAH LINGKUNGAN DALAM PRODUKSI BATIK ORGANIK MANGROVE DAN PENGEMBANGAN DESA WISATA KEBUNDADAP TIMUR - Hastri, Evi Dwi; Romadhan, Siddik; Hopid, Hopid (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
In line with the development direction of Kebundadap Timur Village and the effort to improve the local economy through mangrove tourism development, the community can enhance their economic resilience by creating sustainable employment and entrepreneurship opportunities, such as through ecotourism and the downstream processing of mangroves into organic batik. The potential of mangroves is evident from the diversity of species found in Kebundadap Timur Village, with no fewer than 22 mangrove species recorded. The downstream development of mangroves as the village’s main potential represents a crucial strategy to strengthen market share positioning, increase profitability, and contribute positively to local economic development. This strategy extends beyond the tourism industry to include the batik industry, which is designed to be competitive at local, national, and even global levels. The Women's Empowerment Group (PKK) of Kebundadap Timur Village is engaged in the management of organic mangrove batik, while the Village-Owned Enterprise (BUMDesa) Pasopati focuses on managing mangrove educational tourism. The methodological approach to addressing partner issues involved different focus areas: Partner 1 faced challenges in production and marketing, while Partner 2 needed solutions in promotion and destination development. The outcomes of this initiative include: (1) increased quantity of natural dye and organic hand-drawn batik products by Partner 1, with production achievement rising from 0% to 100%; (2) successful marketing of mangrove-based organic batik through partnership cooperation and digital marketing by Partner 1, also reaching 100% achievement; and (3) increased income-generating activities from WMK tourism through digital promotion and enhanced tourist attraction development by Partner 2, with monthly revenue increasing from IDR 3,000,000 to IDR 5,950,000.Sejalan dengan arah pengembangan Desa Kebundadap Timur dan melihat pada peningkatan Ekonomi Lokal melalui pengembangan wisata mangrove, masyarakat dapat meningkatkan ekonomi lokal dengan menciptakan lapangan kerja dan kewirausahaan berkelanjutan, seperti ekowisata, dan hilirasisi mangrove menjadi batik organik. Potensi mangrove dapat dilihat dari beragamnya jenis mangrove di Desa Kebundadap Timur yakni tidak kurang dari 22 jenis mangrove. Hilirisasi mangrove sebagai potensi utama Desa Kebundadap Timur merupakan strategi penting untuk memperkuat posisi pangsa pasar, meningkatkan profitabilitas, dan memberikan kontribusi positif bagi pembangunan ekonomi lokal. Tidak hanya pada industri pariwista, namun pada industri batik yang dirancang untuk mampu bersaing secara lokal, nasional, hingga global. Kelompok PKK Desa Kebundadap Timur bergerak di bidang tata kelola batik organik mangrove sedangkan Bumdesa Pasopati bergerak di bidang tata kelola eduwisata mangrove. Tahapan metode yang dilakukan untuk memberikan solusi pada permasalahan mitra yakni pada Mitra-1 di bidang produksi dan pemasaran, sedangkan permasalahan mitra-2 yakni pada bidang promosi dan pengembangan destinasi. Luaran kegiatan sebagai hasil yang diperoleh yaitu peningkatan Kuantitas produk pewarna dan batik tulis organik (Mitra 1) berhasil memproduksi dengan capaian dari 0% menjadi 100%, Pemasaran batik organik Mangrove dengan adanya kemitraan kerjasama dan pemasaran digital (Mitra 1) berhasil dengan capaian dari 0% menjadi 100%, dan Peningkatan Income Generating Wisata WMK dengan promosi digital dan pengembangan daya tarik destinasi wisata (Mitra 2) sebelum kegiatan sebesar Rp.3.000.000,-/bulan dan setelah kegiatan Rp.5.950.000,-/bulan.